Anterior cervical discectomy and fusion with zero-profile versus stand-alone cages for two-level cervical spondylosis: A retrospective cohort study - Mu, Guanzhang; Chen, Hao; Fu, Haoyong; Wang, Shijun; Lu, Hailin; Yi, Xiaodong; Li, Chunde; Yue, Lei; Sun, Haolin (Frontiers in Surgery, 2022)
ABSTRACT: OBJECTIVE To assess the long-term clinical and radiological outcomes of zero-profile (ZP) compared with stand-alone (ST) cages for two-level anterior cervical discectomy and fusion (ACDF). METHODS We included 77 patients (39 women and 38 men) who underwent two-level ACDF between May 5, 2016, and May 5, 2020, and who were followed up for at least one year. The subjects were divided into the ST (n = 38) and ZP (n = 39) group. For the evaluation of functional status, Japanese Orthopedic Association (JOA), Neck Disability Index (NDI), and Visual Analogue Scale (VAS) scores were used. Additionally, radiological outcomes and procedure complications were observed at final follow-up. RESULTS Both groups had excellent clinical outcomes at the final follow-up. There were no significant intergroup (ZP vs ST) differences in the fusion rate (91.02% vs 90.79%, P ＞ 0.05) and postoperative dysphagia (15.4% vs 2.6%, P = 0.108). However, the disc height at the final follow-up in the ZP group was higher than that in the ST group (6.86 ± 0.84 vs 6.17 ± 1.03, P = 0.002). The ZP group accomplished a lower loss of cervical lordosis (18.46 ± 4.78 vs 16.55 ± 4.36, P = 0.071), but without reaching statistical significance. CONCLUSIONS ACDF with either ZP or ST cages turns out to be a dependable strategy for two-level ACDF in terms of clinical results. However, compared with the ST, the ZP cage may achieve a significantly lower loss of disc height.